Decision Support System for Selection of Productive Land in Corn Using the SMART Method - Yunike Andrayani; Muslimin B; Annafi Franz (Politeknik Pertanian Negeri Samarinda, 2023)
Indonesia is one of the developing countries which has characteristics in one sector in agriculture, which is one source of income and improves the economy of farmers, but farmers in processing agricultural land are still not maximized as a means of productive plant land. This productive land requires a technology that can assist in land selection, the purpose of this research is to produce a Decision Support System for the Selection of Productive Land in Corn Plants Using a Web-Based Smart Method, and the author wants to implement the Smart method into the selection of productive land for corn plants that is safe in this system requires data that includes data criteria and alternatives. The results of the data are processed using intelligent methods so that it will produce alternative recommendations that have the highest value. this research can help coordinators of agricultural extension centers assist farmers in managing land to be productive.